The Training Problem of Creative Work for Successful Living - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2005)
In educational science research it is little spoken about how a particular learner can easily and reliably carry the best subject mastering success. Even less is written about successful lifestyle creation. It is exigent to organize a purposeful necessity in gaining success. It is possible to achieve this via acknowledging yourself by means of self-reflection and acknowledging activities. In order to obtain this, it is necessary based on its quality to project and improve self-potentiality, plan a concrete action according to circumstances. All this in a condensed way is analysed in this article via answering such questions: 1) how to nurture the success of activity in the parental house? 2) how to work and earn successfully? 3) how to make happiness successfully in your own family? 4) how to establish success in improving relations in the society? 5) how to overcome asociality? Research methods are: home, work, study effecting, its result observation, evaluation, expert accounting, data of the incomplete sentence test, which was performed by adult learners from Alytus anti Utena work marketing training council centers most of whom did not possess successful living.
Keywords: successful living; education; family; society; work